ANALISIS FUNGSI-TUGAS CASE MANAGER DALAM MENGELOLA KASUS PASIEN RAWAT INAP (STUDI KASUS) DI RSUD DELI SERDANG KECAMATAN LUBUK PAKAM KABUPATEN DELI SERDANG TAHUN 2019 - SILVYA WIDYA SANTI; DANIEL GINTING; EVAWANI SILITONGA (LP2MTBM MAKARIOZ, 2019)
Target quality outcomes include reducing patient complaints, increasing patient satisfaction. But the fact that we find, the problem of patient complaints, health services that are still a routine activity, the communication of the responsible doctor is limited to providing therapy, high medical costs are still often found. Professional nurses in hospitals basically have a very dominant role in implementing case management and even have an important role in the healing process. Case managers are generally responsible for the coordination and continuity of patient services or in certain phases of service are clearly identified. The purpose of this study was to analyze the case manager's tasks in managing inpatient cases (case studies). This research was conducted at Deli Serdang District Hospital, Lubuk Pakam District, Deli Serdang Regency in January - July 2019. The type of research in this study was qualitative. The sample in this study was a case manager in Deli Serdang District Hospital with 5 people and 1 head of medical services and 1 head of medical services. The results showed that the case manager's functions consisting of case manager utility assessments, patient manager planning by case manager, facilitation and case manager advocacy at Deli Serdang District Hospital were not yet optimal. Coordination of services conducted by case managers, case manager evaluations and follow-up after discharge planning by case managers at Deli Serdang District Hospital has not gone well. This is due to several factors including the absence of a clear format regarding the functions of case managers, there has never been training on case managers and there is still a lack of case managers who are responsible for 16 inpatient rooms. Case managers should carry out case manager functions on patients who are carried out case management in accordance with the criteria criteria set by SNARS 2017 accompanied by proper and accurate documentation to improve service quality and patient satisfaction.